PENGEMBANGKAN WISER BERBANTUAN MEDIA REKAM TANGKAP LAYAR UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI - Kusmiati, Kusmiati (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2022)
This article aims to describe the importance of improving students' communication skills by developing WISER assisted with screen capture media on Smart Digital Learning (SDL). Communication skill is a skill that needed in today's era of globalization. Good communication skills can lead students to reach their future. However, in reality, there are still many obstacles to this skill. So, a strategy, as well as media, is needed to support its improvement. This study uses classroom action research using two cycles. The research subjects were 29 students of VII graders. The results showed that the students' communication skills in the first cycle with the percentage of completeness of 89.66% increased to 96.55% in the second cycle. Then, the score for students' communication skills from the category good improved to the very good. The conclusion is that the students' communication skills improve by developing WISER (Wondering habits, Investigating skills, Synthezing skills, Expressing skills , and Reflecting habits) assisted by screen capture media of procedure text in learning to present procedure texts for VII grade of SMP Islam Sabilillah Malang.